Magnetic poly(1,8-diaminonaphthalene)-nickel nanocatalyst for the synthesis of antioxidant and antibacterial isoxazole-5(4H)-ones derivatives - Shefa Mirani Nezhad; Seied Ali Pourmousavi; Ehsan Nazarzadeh Zare; Golnaz Heidari; Samanesadat Hosseini; Mahla Peyvandtalab (Heliyon, 2023)
A magnetic poly (1,8-diaminonaphthalene)-nickel (PDAN-Ni@Fe3O4) composite as a multifunctional nanocatalyst was prepared in several steps including (I) synthesis of poly (1,8-diaminonaphthalene) (PDAN), (II) modification of PDAN with NiSO4 (PDAN-Ni) and (III) preparation of magnetic nanocatalyst by iron (I and II) salts in the existence of PDAN-Ni complex (PDAN-Ni@Fe3O4). Fourier-transform infrared spectroscopy (FTIR), elemental analysis (CHNSO), vibrating-sample magnetometer (VSM), X-ray diffraction (XRD), energy-dispersive X-ray (EDX), field emission scanning electron microscope (FESEM), ultraviolet–visible (UV–vis), and thermogravimetric analysis (TGA) were applied to characterize the prepared nanocatalyst. The PDAN-Ni@Fe3O4 was applied as an environmentally friendly nanocatalyst for the isoxazole-5(4H)-ones synthesis via a one-pot reaction between aryl/heteroaryl aldehyde, hydroxylamine hydrochloride, and β-ketoester. The nanocomposite was also used for the synthesis of some new alkylene bridging bis 4-benzylidene-3-methyl isoxazole-5(4H)-ones. The catalyst's reusability, and the antioxidant and antibacterial activities of both catalyst and products, were studied. Results showed that the nanocatalyst and isoxazole-5(4H)-ones have antioxidant activity of 75% and 92%, respectively. In addition, the antibacterial test showed that the nanocatalyst and isoxazole-5(4H)-ones have highly active versus Staphylococcus aureus and Escherichia coli bacteria. The reusability and stability of the nanocatalyst, a medium to higher product yield and conversion, a faster reaction time, and the use of green solvents were a few benefits of this study.